A prospective study of abdominal wall endometriomas: a review of 16 cases - Nalini, Y. Lakshmi; Puvvala, Manipal Kumar; Chandra, A. Sarath; Rajalingam, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Endometriosis is a disorder in which an ectopic endometrial tissue grows outside the uterine cavity. The ectopic endometrium in abdominal wall is called as abdominal wall endometriosis (AWE). AWE is a very rare condition and exact incidence is not known. This is usually known to develop along with previous surgical scars especially following Caesarean section and Hysterectomy. Methods: Retrospective analysis of the patients operated for AWE was done. Data relating to age, symptomology, and previous caesarean section, relation to symptoms with the menstrual cycle, physical examination, surgical treatment and post-operative course was analyzed. Results: 16 patients were operated during the study period of 3 years between September 2013-september 2016.The ages ranged between 20-35 years. Presences of local mass and cyclical pain during menstruation were the main symptoms. Ultrasonography was done in all the cases and CT abdomen was done in few cases (2) to know the exact depth of the mass and to differentiate from other diseases. Wide surgical excision was carried out in all cases. Conclusions: There is definite relationship with AWE and caesarean sections in women.